MPhil in pulmonary haemorrhage in children in Cape Town - Masu, Adelaide Ngina (Department of Paediatrics and Child Health, 2025)
Introduction: Diffuse alveolar haemorrhage (DAH) is a rare condition in childhood which carries high morbidity and mortality. Outcomes are improved by initiating appropriate investigations to ensure early diagnosis and institute correct and timely management. Objectives: To understand the clinicopathological features of DAH and its management on the outcomes of children with this diagnosis. Methods: A descriptive study was conducted on children attending a tertiary centre pulmonology clinic from the period 2000-2022. A review of the clinical data, investigations and lung biopsy results was done and outcomes were reported. Results: Sixteen children were included in the study. The median age at presentation was 1.79 years (IQR 0.48-3.15). At presentation, the median haemoglobulin (Hb)was 5.4 (IQR 3.6-85). Five out of16(31%) had haemoptysis. Seven children showed a pulmonary IgA vasculitis on biopsy. Of the most recent spirometry 5/14 (38.46) had a restrictive pattern. At diagnosis 6/16 (37%) received intravenous methyl-prednisone and 10/16(63%) received oral prednisone as treatment. The children who received more than one immunosuppressant agent as management were 14/16 (87%). Ten out of 16 children are in remission. Conclusion: Early diagnosis of DAH and multidrug management seems to improve outcomes. The finding of isolated IgA vasculitis on lung biopsy associated with DAH has not been well described.